METAMAFIC ROCKS OF THE TANA BELT, KOLA PENINSULA: ISOTOPIC AGE AND PT CONDITIONS - Perchuk L.L.; Yapaskurt V.O.; Krotov A.V.; Kramers J.D. (My University, 2006)
Mica schists of the Korva Tundra Group (~1.91 Ga) of the Tana Belt were buried at the middle crustal level and later exhumed simultaneously with granulites of the Lapland Complex (~1.91 Ga). The Kandalaksha Group (KG) is composed of higher-temperature rocks, but their geodynamic evolution is similar to that of the Korva Tundra Group. Since the KG rocks have not been previously dated in this area, their synchronous metamorphism with Lapland granulites has not been proved. To solve this problem, metamorphic PT conditions and U–Pb zircon ages were determined for two KG samples taken in the Pados–Yavr interfluve. The results are presented in this work.
Keywords: Tana belt; Kola peninsula